'Active integration': sport clubs taking an active role in the integration of refugees. Issue 2 (2nd April 2020) - Doidge, Mark; Keech, Marc; Sandri, Elisa
ABSTRACT: In the context of the global migrant and refugee crisis there is considerable enthusiasm for the notion that participation by migrants of refugee background in community sport can play a role in fostering a sense of community belonging. Sport potentially is an opportunity for refugees to integrate (with each other and host communities). Community sports organisations in the UK - and specifically sports clubs - continually face challenges to devote resources to social policy outcomes beyond increasing sport participation. This article argues that the active approach of coaches, volunteers and managers to consciously manage inclusive sport activities is central for the integration of refugees. Utilising a mixed methods approach, this study analysed the impact of one sports club that used table tennis to promote the active integration of refugees. The study found three significant areas of impact: first, an active approach from coaches can facilitate integration; second, such an approach should be conducted in a safe, enjoyable and welcoming environment; and that sport is a positive social activity for youths with a refugee background if the focus of the activity centres on fun and social interaction, rather than just sporting skills.